2017
DOI: 10.4265/bio.22.17
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Total Petroleum Hydrocarbon (TPH) in Contaminated Soil Using <i>Bacillus pumilus</i> MVSV3

Abstract: A study on bioremediation of soil contaminated with petroleum sludge was performed using Bacillus pumilus/MVSV3 Accession number JN089707 . In this study, 5 kg of agricultural soil was mixed well with 5% oil sludge and fertilizers containing nitrogen, phosphorus and potassium-N:P:K . The treatment resulted in 97% removal of total petroleum hydrocarbon TPH in 122 d in bacteria mixed contaminated soil when compared to 12% removal of TPH in uninoculated contaminated soil. The population of the microorganism remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
5
0
1
Order By: Relevance
“…are more tolerant to high concentrations of polycyclic aromatic hydrocarbons in soil due to their resistant endospores, so the isolates belonging to the Bacillus sp. could be effective in the removal of PAHs in the contaminated soils [2,[38][39][40][41]. e 34 Bacillus isolates in this study are able to grow in 24 hours or 48 hours on BH medium supplemented with different carbon sources (gasoline, diesel oil, benzene, hexane and olive oil) 2% (v/v).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…are more tolerant to high concentrations of polycyclic aromatic hydrocarbons in soil due to their resistant endospores, so the isolates belonging to the Bacillus sp. could be effective in the removal of PAHs in the contaminated soils [2,[38][39][40][41]. e 34 Bacillus isolates in this study are able to grow in 24 hours or 48 hours on BH medium supplemented with different carbon sources (gasoline, diesel oil, benzene, hexane and olive oil) 2% (v/v).…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that Bacillus sp. are among the most predominant isolates of crude oil [2,40,41]. e phenotypic and biochemical characteristics of the 34 isolates were related and oriented towards genus Bacillus.…”
Section: Discussionmentioning
confidence: 97%
“…Petroleum-degrading bacteria can be used for bioremediation of soil contaminated with petroleum sludge, which is the oily sludge generated in refineries when inlet and outlet tanks are cleaned. Disposal of the sludge causes environmental issues as well as human health concerns, but bacterial remediation of contaminated soil can restore its ability to support healthy growth of crop plants (Varma et al, 2017). Successful, and rapid, degradation rates of Total Petroleum Hydrocarbon (TPH) has also been demonstrated by mixed populations of petroleum-degrading bacteria with white-rot fungi grown in solid-state fermentation.…”
Section: Fungi For Bioremediationmentioning
confidence: 99%
“…在沾3油藏中还发现大量的厚壁菌门, 主要包括芽 孢杆菌纲、梭菌纲以及柔膜菌纲. 目前已有大量研究 发现了芽孢杆菌纲以及梭菌纲对石油烃具有较强的降 解能力 [33,34] , 并能够被用于油藏开采或土壤、海洋石 油污染的修复, 因为它们能够快速适应石油污染环境 并利用石油进行自身生长代谢 [34] ; 其代谢产物不仅能 够起到原油乳化剂的作用 [33] , 还能够为其他在油藏环 境中生存但不能利用烷烃的群落提供营养 [35] . 因此, 厚 壁菌门对油藏微生物群落的构建及稳定起着十分重要 的作用.…”
Section: 微生物组α多样性unclassified